Genome Sequence Analysis of Clostridium chauvoei Strains of European Origin and Evaluation of Typing Options for Outbreak Investigations - Thomas, Prasad; Abdel-Glil, Mostafa Y.; Eichhorn, Inga; Semmler, Torsten; Werckenthin, Christiane; Baumbach, Christina; Murmann, Wybke; Bodenthin-Drauschke, Anne; Zimmermann, Pia; Schotte, Ulrich; Galante, Domenico; Slavic, Durda; et al. (Frontiers in Microbiology, 2021)
Black quarter caused by Clostridium (C.) chauvoei is an important bacterial disease that affects cattle and sheep with high mortality. A comparative genomics analysis of 64 C. chauvoei strains, most of European origin and a few of non-European and unknown origin, was performed. The pangenome analysis showed limited new gene acquisition for the species. The accessory genome involved prophages and genomic islands, with variations in gene composition observed in a few strains. This limited accessory genome may indicate that the species replicates only in the host or that an active CRISPR/Cas system provides immunity to foreign genetic elements. All strains contained a CRISPR type I-B system and it was confirmed that the unique spacer sequences therein can be used to differentiate strains. Homologous recombination events, which may have contributed to the evolution of this pathogen, were less frequent compared to other related species from the genus. Pangenome single nucleotide polymorphism (SNP) based phylogeny and clustering indicate diverse clusters related to geographical origin. Interestingly the identified SNPs were mostly non-synonymous. The study demonstrates the possibility of the existence of polymorphic populations in one host, based on strain variability observed for strains from the same animal and strains from different animals of one outbreak. The study also demonstrates that new outbreak strains are mostly related to earlier outbreak strains from the same farm/region. This indicates the last common ancestor strain from one farm can be crucial to understand the genetic changes and epidemiology occurring at farm level. Known virulence factors for the species were highly conserved among the strains. Genetic elements involved in Nicotinamide adenine dinucleotide (NAD) precursor synthesis (via nadA, nadB and nadC metabolic pathway) which are known as potential anti-virulence loci are completely absent in C. chauvoei compared to the partial inactivation in C. septicum. A novel core-genome MLST based typing method was compared to sequence typing based on CRISPR spacers to evaluate the usefulness of the methods for outbreak investigations.